Hubungan Ansietas dengan Mekanisme Koping pada Pasien Diabetes Melitus di Semarang: The Relationship of Anxiety and Coping Mechanisms in Diabetes Mellitus Patient - Senti Sene; Betie Febriana; Wahyu Endang Setyowati; Dwi Heppy Rochmawati (Jurnal Keperawatan Berbudaya Sehat, 2025)
Diabetes Mellitus is a chronic disease that significantly impacts patients' mental health, particularly their anxiety levels. This study aims to investigate the relationship between anxiety and coping mechanisms among diabetes mellitus patients in Semarang. This study employed the DASS 42 questionnaire to assess anxiety levels and coping mechanisms in patients. The results showed a significant correlation between anxiety levels and coping mechanisms in diabetes mellitus patients. The study revealed that patients with higher anxiety levels tend to use less adaptive coping mechanisms, which can exacerbate their health conditions. This study concludes that effective anxiety management is crucial in enabling diabetes mellitus patients to employ more adaptive coping mechanisms. Therefore, healthcare providers should offer psychological support to help reduce anxiety levels among these patients, ultimately improving their overall health outcomes.